2020
DOI: 10.3390/antibiotics9080459
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-DAD and UHPLC/QTOF-MS Analysis of Polyphenols in Extracts of the African Species Combretum padoides, C. zeyheri and C. psidioides Related to Their Antimycobacterial Activity

Abstract: Combretum padoides Engl. & Diels, C. psidioides Welv. and C. zeyheri Sond. are used forthe treatment of infections and tuberculosis related symptoms in African traditional medicine. In orderto verify these uses, extracts were screened for their growth inhibitory eects against M. smegmatisATCC 14468. Ultra-high pressure liquid chromatography coupled to quadrupole time-of-flightmass spectrometry (UHPLC/QTOF-MS) and GC-MS were used to investigate the polyphenoliccomposition in the active extracts. The lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 101 publications
0
19
0
Order By: Relevance
“…Most studies on the antibacterial effects of Combretum species on bacteria that cause respiratory diseases have used only one bacterium, either Pseudomonas aeruginosa or Klebsiella pneumoniae, although a multitude of bacterial strains, such as Staphylococcus aureus, Streptococcus pneumoniae, Haemophilus influenza, Corynebacterium diphteriae, Bordetella pertussis, and Mycobacterium tuberculosis are known to cause respiratory diseases [22]. Moreover, to date, C. psidioides, C. padoides, C. zeyheri, C. hartmannianum, C. molle, C. apiculatum, C. imberbe, and C. hereroense are the species that have so far been screened for their antimycobacterial effects, although there are still many Combretum species used for tuberculosis (TB) that have not been scientifically validated [23,51,107,[110][111][112][113]. For example, C. micranthum is used for TB in Guinean traditional medicine, but there is no literature available about its antimycobacterial potential.…”
Section: Antibacterial and Antifungal Effects Of Combretum Spp Extractsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies on the antibacterial effects of Combretum species on bacteria that cause respiratory diseases have used only one bacterium, either Pseudomonas aeruginosa or Klebsiella pneumoniae, although a multitude of bacterial strains, such as Staphylococcus aureus, Streptococcus pneumoniae, Haemophilus influenza, Corynebacterium diphteriae, Bordetella pertussis, and Mycobacterium tuberculosis are known to cause respiratory diseases [22]. Moreover, to date, C. psidioides, C. padoides, C. zeyheri, C. hartmannianum, C. molle, C. apiculatum, C. imberbe, and C. hereroense are the species that have so far been screened for their antimycobacterial effects, although there are still many Combretum species used for tuberculosis (TB) that have not been scientifically validated [23,51,107,[110][111][112][113]. For example, C. micranthum is used for TB in Guinean traditional medicine, but there is no literature available about its antimycobacterial potential.…”
Section: Antibacterial and Antifungal Effects Of Combretum Spp Extractsmentioning
confidence: 99%
“…Moreover, there are several herbal formulations of plant extracts from the Pteleopsis and Combretum species, in both African and international markets, that are briefly discussed in this review [20]. In accordance with their traditional uses for the treatment of infection, numerous in vitro studies have confirmed that African Combretum species possess antibacterial and antifungal properties [22,23]. Species of the genus Pteleopsis have been studied to a lesser extent, although there are reports confirming the antimicrobial activities of P. myrtifolia and P. suberosa [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are first isolated from the South African Combretum caffrum specie [59]. Other Combretum species also contain these molecules [60,61]. Combretastatins are simple compounds formed of two phenyl rings linked by a chain of two carbon atoms.…”
Section: Potential Anticancer Compounds Isolated From Combretum Speciesmentioning
confidence: 99%
“…This study further extends the range of compounds that are produced by the genus Simplicillium. Fyhrquist et al [ 6 ], who also followed the bioactivity-guided fractionation approach, used water and solvents (methanol, butanol and chloroform) to extract several phenolic and polyphenolic compounds from three species of the Combretum genus in a search for anti-mycobacterial activity. Active extracts were analyzed by ultrahigh-pressure liquid chromatography coupled to quadrupole time-of-flight mass spectrometry (UHPLC/QTOF–MS) and GC–MS.…”
mentioning
confidence: 99%